Research on the Deformation and Failure Mechanism of Flexible Formwork Walls in Gob-Side-Entry Retaining of Ultra-Long Isolated Mining Faces and Pressure Relief-Control Technology via Roof Cutting - Heng Wang; Junqing Guo (Applied Sciences)
To resolve the critical issues of severe deformation, structural failure, and maintenance difficulties in the advanced reuse zone of gob-side-entry retaining roadways under pillarless mining conditions in ultra-long fully mechanized top-coal caving isolated mining faces, this study proposes a surrounding rock control technology incorporating pressure relief through roof cutting. Taking the 3203 ultra-long isolated mining face at Nanyang Coal Industry as the engineering case, an integrated methodology combining laboratory experiments, theoretical analysis, numerical simulations, and industrial-scale field trials was implemented. The deformation and failure mechanism of flexible formwork walls in gob-side-entry retaining and the fundamental principles of pressure relief via roof cutting were systematically examined. The vertical stress variations in the advanced reuse zone of the retained roadway before and after roof cutting were investigated, with specific focus on the strata pressure behavior of roadways and face-end hydraulic supports on both the wide coal-pillar side and the pillarless side following roof cutting. The key findings are as follows: ① Blast-induced roof cutting reduces the cantilever beam length adjacent to the flexible formwork wall, thereby decreasing the load per unit area on the flexible concrete wall. This reduction consequently alleviates lateral abutment stress and loading in the floor heave-affected zone, achieving effective control of roadway surrounding rock stability. ② Compared with non-roof cutting, the plastic zone damage area of surrounding rock in the gob-side entry retained by flexible formwork concrete wall is significantly reduced after roof cutting, and the vertical stress on the flexible formwork wall is also significantly decreased. ③ Distinct differences exist in the distribution patterns and magnitudes of working resistance for face-end hydraulic supports between the wide coal-pillar side and the pillarless gob-side-entry retaining side after roof cutting. As the interval resistance increases, the average working resistance of hydraulic supports on the wide pillar side demonstrates uniform distribution, whereas the pillarless side exhibits a declining frequency trend in average working resistance, with an average reduction of 30% compared to non-cutting conditions. ④ After roof cutting, the surrounding rock deformation control effectiveness of the track gateway on the gob-side-entry retaining side is comparable to that of the haulage gateway on the 50 m wide coal-pillar side, ensuring safe mining of the working face.